2013
DOI: 10.1371/journal.pone.0068886
|View full text |Cite|
|
Sign up to set email alerts
|

Systems Biology Analysis of Zymomonas mobilis ZM4 Ethanol Stress Responses

Abstract: Background Zymomonas mobilis ZM4 is a capable ethanologenic bacterium with high ethanol productivity and ethanol tolerance. Previous studies indicated that several stress-related proteins and changes in the ZM4 membrane lipid composition may contribute to ethanol tolerance. However, the molecular mechanisms of its ethanol stress response have not been elucidated fully.Methodology/Principal FindingsIn this study, ethanol stress responses were investigated using systems biology approaches. Medium supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
71
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 70 publications
8
71
0
Order By: Relevance
“…Therefore, we systematically tested expression levels of all identified sRNA candidates under the ethanol stress conditions. We chose a 5% (vol/vol) ethanol supplement to the medium as the ethanol stress conditions given that 6% (vol/vol) ethanol was previously shown to affect cell viability dramatically (44). We confirmed that Zms2, Zms6, and Zms18 showed differential expression under ethanol stress conditions (Fig.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, we systematically tested expression levels of all identified sRNA candidates under the ethanol stress conditions. We chose a 5% (vol/vol) ethanol supplement to the medium as the ethanol stress conditions given that 6% (vol/vol) ethanol was previously shown to affect cell viability dramatically (44). We confirmed that Zms2, Zms6, and Zms18 showed differential expression under ethanol stress conditions (Fig.…”
supporting
confidence: 60%
“…Most of the newly found genes in our study are related to metabolism and cellular processes. Our analysis showed that alcohol dehydrogenase, which was downregulate under ethanol treatment conditions (44), was less abundant in late exponential phase under aerobic conditions (see Table S5). We also confirmed that the Hfq gene (ZMO0347) was more abundant under anaerobic conditions.…”
Section: Discussionmentioning
confidence: 81%
“…It demonstrated the high ethanol fermentability (ethanol yield above 75% and productivity above 1.1 g/L/h) and strong tolerance to high temperature (42°C), high lignocellulosic solids loading (35%), and inhibitors (acetic acid, furfural, and HMF) during the simultaneous saccharification and fermentation of the pretreated corn stover, wheat straw, rice straw and other agricultural biomass (Chu et al, ; Zhang et al, , ). Although Z. mobilis demonstrates advantages in ethanol fermentation (Yang et al, ), the low tolerance to inhibitory compounds makes it is less frequently used when the inhibitor is at a high level (Su et al, ; Zhang and Lynd, ). The tolerance of Z. mobilis to furans and weak acids had been investigated extensively (Dong et al, ; Skerker et al, ; Yang et al, , ), but few studies focus on the toxic effect of phenolic inhibitors on Z. mobilis .…”
mentioning
confidence: 99%
“…Systems biology datasets published for Z. mobilis were collected and analyzed to identify the potential ethanol‐inducible promoters. Since Z. mobilis produces ethanol gradually, which usually reaches the peak when entering the stationary phase with the consumption up of carbon sources such as glucose, native ethanol‐inducible promoters probably can be identified by selecting differentially expressed genes at the late stationary growth stage or under ethanol stress conditions . Genes with at least twofold changes in these conditions were selected for Veen analysis to identify common genes, and promoters of these genes were considered as candidate‐inducible promoters (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Control1, p1ZMRG, and p2ZMRG represent the control which cultured in normal condition. Log represents exponential phase, Sta represents stationary phase, EtOH means ethanol‐induced conditions .…”
Section: Resultsmentioning
confidence: 99%